Functional - Stylistic Language Standards Analysis and Methodology in Aspect Issues (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes the linguostylistic features of the functional styles of the Uzbek language, the normative or non-normative situations in the manifestation of these features on the example of a stylistic norm. The common and different aspects of the stylistic norm among other language and speech norms are shown.